Banking: A New Monetarist Approach - Gu, C.; Mattesini, F.; Monnet, C.; Wright, R. (Review of Economic Studies, 2013)
We develop a model where: (i) banks take deposits and make investments; (ii) their liabilities facilitate third-party transactions. Other models have (i) or (ii), not both, although we argue they are intimately connected: we show that they both emerge from limited commitment. We describe an environment, characterize desirable allocations, and interpret the outcomes as banking arrangements. Banks are essential: without them, the set of feasible allocations is inferior. As a technical contribution, we characterize dynamically optimal credit allocations with frictions, show they involve backloading, and analyse how this interacts with banking. We also confront the theory with economic history.